Failure Prediction Capability of Generalized Plastic Work Criterion - Aksen, Toros Arda; Sener, Bora; Firat, Mehmet (ELSEVIER SCIENCE BV, 2020)
In this study, failure prediction capability of the generalized plastic work criterion was evaluated. Criterion was applied to the uniaxial tensile and Nakajima stretch forming tests to predict the forming limits of an advanced high strength steel sheet. Firstly, critical damage value of the material was calculated for two different cases. Energy value till uniform elongation range was considered for in the first case, while total energy value was considered in the second case. Finite element simulations of the uniaxial tensile and Nakajima stretch forming tests were performed for both cases. The fracture strain in the uniaxial tensile test and limit strains of each Nakajima sample were predicted and the predicted results were compared with the experimental results. Comparisons showed that the onset of the diffuse necking and the fracture strain were predicted successfully in the uniaxial tensile test. However, it was observed from Nakajima tests that limit strains at the left side of the forming limit diagram (FLD) were predicted successfully by the criterion, while they werent accurately predicted at the right side of the FLD. (C) 2020 The Authors. Published by Elsevier Ltd.
Keywords: generalized plastic work; uniaxial tensile test; Nakajima stretch forming test; finite element simulation; limit strain; DUCTILE FRACTURE; GROWTH; Engineering; Materials Science